Glyphosate ingestion causing multiple organ failure: a near-fatal case report. - Picetti, Edoardo; Generali, Michela; Mensi, Francesca; Neri, Giampaolo; Damia, Roberta; Lippi, Giuseppe; Cervellin, Gianfranco (Acta Biomedica Atenei Parmensis, 2018)
A 55 years old man self-presented to our Emergency Department (ED) reporting an attempted suicide by cutting the left forearm veins and ingesting approximately 200 mL of an herbicide (Myrtos®, containing 36% of glyphosate as isopropylamine salt). Laboratory tests showed metabolic acidosis. Hydration with normal saline and alkalinization with sodium bicarbonate was started according to suggestion of the poison control center, since an antidote was unavailable. Cardiorespiratory condition gradually worsened, so that non-invasive positive pressure ventilation (NIPPV) was applied and infusion of fluids was established. Nevertheless, the patient deteriorated and he needed to be transferred to the Intensive Care Unit (ICU), where he underwent orotracheal intubation and invasive mechanical ventilation. Noradrenaline and adrenaline were infused and fluid resuscitation with crystalloids was incremented. An esophagogastroduodenoscopy (EGD) showed diffuse mucosal erosions of upper digestive tract. No signs of visceral perforation were found during ICU stay. In the following days, the clinical conditions improved and a new EGD showed marked improvement of erosive lesions. After 12 days of ICU stay, the patient was extubated and then transferred to the Psychiatric Unit, in good clinical conditions. Gliphosate ingestion is associated with rapid development of multiple organ failure (MOF). Since an effective antidote is unavailable, major attention should be placed to aggressive life-support care and careful monitoring of complications.